BIBLIOTECAS UNIVERSITÁRIAS FEDERAIS DA AMAZÔNIA: desbravando fronteiras, administrando improvisos - Silva, Angela Maria Moreira (2009)
This is a research into the History of Federal University Libraries of Northern Region, which empirical field was the Libraries of the States of Acre, Amapá, Rondônia and Roraima. The interlude considered on this research comprehends the period between 1970 and 2000, having as context the whole predominant aspects that have influenced universities and their Brazilian university libraries, between the military dictatorship and Fernando Henrique Cardoso government. The research aims to understand which factors have influenced the construction and the performance of Federal university libraries in Amazonia during their history; in which way the public measures have influenced their performance and whether the employee´s mentality and way of acting have conditioned the performance of those libraries. In the attempt of answering those questions, the research is anchored in Pierre Bourdieu' s methodological and theoretical concepts, mainly his perception of objective relations into the social spaces (field); notion of internalized social structures (habitus); and his concepts of capital. Besides the studied bibliography, it was used the technique of oral testimonials with the research agents, who were the auxiliaries, directors and librarians that have worked in the investigated libraries. After the analysis of the bibliographic data and the concept's operationalization, the study concludes that government policies have had a great impact over the studied libraries. It has also been inferred, however, that the performance of their employees, mainly the librarians, was determinant to the structuration of the precarious conditions in which those libraries are found.